Sociocultural Perspectives on Youth Ethical Consumerism (Cultural Studies of Science Education,, 2018)
This exciting new book advances current practice-based and theoretical knowledge around how youth defines and engages with consumerism to provoke a larger conversation within science and environmental education. It is also geared towards unveiling those literacy praxes that can assist youth to adopt more ethically-oriented consumerist habits. More specifically, this book studies how youth's participation in the global consumer market intersects with media technologies, new literacies, as well as science and the environment from sociocultural perspectives. In addition, it considers how school science has mediated youth participation in hyper-consumerism, from food and technology to shelter and transportation. This important and timely book is a must-read for those interested in topics such as critical youth studies, critical media literacy, STEM, arts-based research, STSE education, citizenship education, cultural studies, policy studies, curriculum studies, socio-scientific issues, technology, sustainability, food studies, social justice, poverty, and consumer behaviour. A wide range of science, technology and environmental educators from Australia, Brazil, Canada, Netherlands and the United States have combined their perspectives to produce this exciting, innovative, timely and important book. It should be essential reading for all teachers, teacher educators and curriculum developers keen to address key issues raised by a commitment to assist students in refining their understanding of what constitutes socially, culturally, ethically and politically responsible consumer practices and supporting them in formulating and engaging in effective individual and collective action. Derek Hodson, Emeritus Professor of Science Education, Ontario Institute for Studies in Education (OISE), University of Toronto, Professor of Science Education at The University of Auckland (New Zealand), and Founding Editor of the Canadian Journal of Science, Mathematics and Technology Education (CJSMTE). The authors in the book deconstruct and analyse intricate economic, sociopolitical and affective networks that are behind the cycles of production, distribution and consumption of objects that are present in youngsters' daily lives and their attitudes towards them. Apart from breaking new ground by proposing and discussing socioculturally informed research about the topic, the book connects with pedagogical approaches that value critical perspectives on the nature of the relationship between science, technology, society and environment. It is a must-read for both researchers and practitioners interested in issues related to sustainability and citizenship education. Isabel Martins, Professor of Science Education, Universidade Federal do Rio de Janeiro/ Federal University of Rio de Janeiro (UFRJ). .